Character Characters in the Novel Putri Komodo by Michael Yudha Winarno - Reva Deviana; Rian Hidayat (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
Imaginative literary works are the result of the wishful thinking of an author. The author describes a picture of a person's life through novels. This research is entitled "The Character of the Character in the Novel Putri Komodo by Michael Yudha Winarno". The problems described in this study are: (1) What is the character of the main character, the character of additional characters, (2) How does the author describe the character of the character in the novel Putri Komodo by Michael Yudha Winarno. This study aims to describe, and analyze: Characteristics in the novel Putri Komodo by Michael Yudha Winarno. The author uses the theory of character in prose fiction from Aminuddin (2014) and Burhan Nurgiyantoro (2012). This study uses a qualitative approach with a descriptive method. The data collection technique is hermeneutic technique. The data validity technique used triangulation technique. The data sources used are the entire contents of the novel Putri Komodo by Michael Yudha Winarno. The data taken in this study is the form of words and sentences that describe the character's character. The results of the research on the character of the character in the novel Putri Komodo by Michael Yudha Winarno, there is the character of the main character, namely Fanty, which is described by the author analytically (directly) and dramatic (indirectly). Additional characters Laila is described by the author analytically (directly), Rosa is described by the author analytically (directly), Mama is described by the author analytically (directly), Father is described by the author analytically (directly), Camelia, is described by the author analytically (directly), Sister Gracia the author is described analytically (directly), Grandma Ato is described by the author analytically (directly), Udis is described by the author analytically (directly), Pak Haji Sobari is described by the author analytically (directly).